2010
DOI: 10.1177/0734282910366842
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Devereux Early Childhood Assessment Clinical Form in Low-Income Hispanic American Bilingual Preschool Children

Abstract: The Devereux Early Childhood Assessment Clinical Form (DECA-C) is the first instrument to measure the social-emotional resilience of young children from ages 2 to 5 years. This study is an important step toward gathering validity evidence for the teacher-rated DECA-C. This is the first study to investigate the DECA-C factor structure and the first to examine its use with low-income Hispanic American bilingual preschoolers. The one-factor, three-factor, and higher-order three-factor models were tested for the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 9 publications
4
14
0
Order By: Relevance
“…In a study examining the validity of another type of DECA (LeBuffe & Naglieri, 1999a) instrument, DECA-C (LeBuffe & Neglieri, 2003), Oades-Sese et al (2010) found results similar to those reported here. Their findings and conclusions support our concern regarding DECA’s validity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In a study examining the validity of another type of DECA (LeBuffe & Naglieri, 1999a) instrument, DECA-C (LeBuffe & Neglieri, 2003), Oades-Sese et al (2010) found results similar to those reported here. Their findings and conclusions support our concern regarding DECA’s validity.…”
Section: Discussionsupporting
confidence: 83%
“…Nonetheless, additional research regarding DECA’s (LeBuffe & Naglieri, 1999a) reliability and validity are emerging, and researchers argued that a need still exists for further investigation of its psychometric properties, both with newer methodologies and with additional populations (Jaberg et al, 2009; Lien & Carlson, 2009). For example, Oades-Sese, Kaliski, and Weiss (2010) found a “poor model fit” (p. 357) based on their research on DECA-C (LeBuffe & Neglieri, 2003) in their sample of low income, bilingual Hispanic preschoolers. Their results demonstrated an inability to provide statistical evidence for the instrument’s validity.…”
mentioning
confidence: 99%
“…Nickerson and Fishman (2009) showed that the DESSA scores have strong evidence of convergent validity with measures of similar constructs, such as the scores of the Behavioral and Emotional Rating Scales-2 (BERS-2; Epstein, 2004) and the Behavior Assessment System for Children-2 (BASC-2; Reynolds & Kamphaus, 2004). To the best of our knowledge, no study has assessed convergent evidence of validity with outcomes important for school, or validated the interpretation of the DESSA scores, among lowincome children, although these associations have been evaluated using other measures and samples (e.g., Oades-Sese et al, 2010).…”
Section: The Teacher-rated Dessamentioning
confidence: 99%
“…Social emotional competence supports children’s capacity to succeed in the face of poverty-rated challenges (Oades-Sese, Kaliski, & Weiss, 2010). Defined as the ability to work well socially and emotionally with others from diverse backgrounds and act in a responsible and respectful manner (Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011; Greenberg et al, 2003), social emotional competence predicts personal, social, and academic success among children, including those from low-income backgrounds (Elias, O’Brien, & Weissberg, 2006; Payton et al, 2008).…”
mentioning
confidence: 99%
“…The DECA assessments have a growing research base supporting their technical adequacy including examinations of both reliability and validity (e.g., Barbu, Levine-Donnerstein, Marx, & Yaden, 2012; LeBuffe & Shapiro, 2004; Lien & Carlson, 2009; Oades-Sese, Kaliski, & Weiss, 2010; Ogg, Brinkman, Dedrick, & Carlson, 2010). However, no information about the long-term stability of DECA or DECA-P2 could be located within the literature despite recommendations in the administration manual to collect ratings 3 times per year to monitor a preschooler’s social, emotional, and behavioral progress (LeBuffe & Naglieri, 2012).…”
mentioning
confidence: 99%